Coral reef health evaluation on Pramuka Island: Conservation challenges and opportunities in the Seribu Islands Area: Evaluasi kesehatan terumbu karang di Pulau Pramuka: Tantangan dan peluang konservasi di Kawasan Kepulauan Seribu - Wahjoedi, Iqbal Raihansyah Kusuma; Jagadhita, I Gusti Putu Yudhistira; Edtri, Dewanti Puti; Sachio, Nikolas; Sholichah, Mar’atus; Santanu, Haekal Fathur Bayu; Hutagaol, Irvan Davi; Musa, Albi Muhamad Taufik; Yudha, Firsta Kusuma (Habitus Aquatica, 2025)
Pramuka Island is one of the islands in the Thousand Islands which is the administrative center. Coral reef ecosystem is known as the most beautiful and charming underwater ecosystem and has the richest community on earth. Government of Thousand Islands utilized this as local marine tourism. However, tourism activities have the potential to affect the condition of the coral reef ecosystem. Coral reef ecosystem condition monitoring are carried out to prevent environmental damage. Observation of coral reef data was carried out using the Line Intercept Transect (LIT) method which was modified according to the needs of data observation. The percentage of basic substrate cover is dominated by abiotic, hard coral, and algae categories. The condition of coral reefs in the observation location is classified as moderate. There are 2 observation stations with good coral reef cover, namely APL (Marine Protected Areas) and SPG (South of Roast Island). Locations with poor cover categories are found in BPR (West of Scout Island) and TEP (Cape Eagle Scout).